1999
DOI: 10.1021/es9901765
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Transformation of Bound Trinitrophenyl Residues and Free TNT during a Bioremediation Process Analyzed by Immunoassay

Abstract: To follow the fate of bound metabolites of TNT in soil, a synthetic trinitrophenyl residue covalently linked to humic acids was used as model compound. A selective monoclonal antibody was able to detect chemical changes of the nitro groups of the bound residues. The general possibility of reductive transformations of nitro groups of bound molecules and the reductions rates should be determined. In comparison to the reduction of free TNT and its metabolites, the reductive transformation of the bound trinitrophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 29 publications
1
9
1
Order By: Relevance
“…It has been shown that intestinal microorganisms are effective in reducing TNT through an oxygen‐insensitive NAD(P)H nitroreductase (Bryant and DeLuca, 1991). After incubation in the presence of anaerobic microorganisms, 4ADNT was the major nitroaromatic compound identified by HPLC which corresponded to results from Achtnich et al (1999b) and Bruns‐Nagel et al (2000) However, when catechol was added as a model humic substance in the presence or absence of laccase, the portion of reduced nitroaromatics was considerably lower (Table 1). During the anaerobic phase, the vast majority of the nitroaromatics resided in the solution and were completely extractable.…”
Section: Discussionsupporting
confidence: 60%
“…It has been shown that intestinal microorganisms are effective in reducing TNT through an oxygen‐insensitive NAD(P)H nitroreductase (Bryant and DeLuca, 1991). After incubation in the presence of anaerobic microorganisms, 4ADNT was the major nitroaromatic compound identified by HPLC which corresponded to results from Achtnich et al (1999b) and Bruns‐Nagel et al (2000) However, when catechol was added as a model humic substance in the presence or absence of laccase, the portion of reduced nitroaromatics was considerably lower (Table 1). During the anaerobic phase, the vast majority of the nitroaromatics resided in the solution and were completely extractable.…”
Section: Discussionsupporting
confidence: 60%
“…The observed unavailability of TNT in the high organic matter soil could be due to an irreversible binding (chemisorption) of TNT and its metabolites to the humic fraction of the soil organic matter (Daun et al, 1998). As found in a previous study performed by Achtnich et al (1999), it is also possible that covalent binding of partially reduced TNT metabolites to the soil organic matter is an important immobilization mechanism. Furthermore, Daun et al (1998) indicated that the soil organic matter (humic acids) has greater specific binding capacity for TNT and its metabolites than the clay fraction of the soil.…”
Section: Exhibit 3 Probability Plot Of Pyrene Standardsmentioning
confidence: 63%
“…The electron withdrawing properties of nitro groups on DNTs makes them resistant to chemical or biological oxidation and to hydrolysis 3. Consequently, DNTs are environmentally persistent and make remediation of waste streams and contaminated ground water difficult.…”
Section: Introductionmentioning
confidence: 99%